Gluten Sensitivity and Neurological Illness - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The frequency of IgG and IgA antigliadin antibodies, a measure of cryptic gluten sensitivity, and celiac disease was studied using ELISA in 147 adult patients admitted to the Royal Hallamshire Hospital, Sheffield, UK, for neurologic investigation.